Management of severe renal disease in anti-neutrophil-cytoplasmic-antibody-associated vasculitis: the place of rituximab and plasma exchange?. (2nd February 2022) - Morel, Pauline; Karras, Alexandre; Porcher, Raphaël; Belenfant, Xavier; Audard, Vincent; Rafat, Cédric; Hanouna, Guillaume; Beaudreuil, Séverine; Vilain, Cédric; Hummel, Aurélie; Terrier, Benjamin; Pillebout, Evangeline; et al.
Abstract: Objective: The optimal induction therapy for severe glomerulonephritis of ANCA-associated vasculitis (AAV) is debated. We compared the efficacy of glucocorticoid and rituximab (RTX) or CYC induction therapy for severe AAV-related glomerulonephritis and evaluated the potential benefit of plasma exchange (PE) as adjunct therapy to CYC. Methods: This retrospective, multicentre study included AAV patients with severe renal active disease (serum creatinine level ≥350 µmol/l and/or estimated glomerular filtration ratio ≤15 ml/min/1.73 m 2 ). Propensity-score analysis was used to adjust for potential confounders. Results: Between 2005 and 2017, 153 patients with AAV-related glomerulonephritis were studied (96 [60%] men; mean [s .d .] age 63 [13.1] years): 19 (12%) were treated with RTX and 134 (88%) with CYC. Remission rates did not differ between RTX- and CYC-treated groups. Although more patients with RTX than CYC were dialysis-free at month (M) 12 (79% vs 68%), the difference was not significant after adjustment. Among 134 patients with CYC-treated glomerulonephritis, 76 (57%) also had PE. M3 and M6 remission rates were comparable for weighted CYC groups with or without PE. For weighted groups, the dialysis-free survival rate with CYC was higher with than without PE at M6 (72% vs 64%; odds ratio 2.58) and M12 (74% vs 60%; odds ratio 2.78) reaching statistical significance at M12. Conclusion: We could not find any difference between RTX and CYC as induction therapy for patients with severe AAV-related glomerulonephritis. In patients receiving CYC induction regimen, the addition of PE conferred short-term benefits with higher dialysis-free rate at M12.